2020
DOI: 10.1186/s12967-020-02243-w
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a panel of cancer stem cell markers enhances the predictive capability of the progression and recurrence in the early stage cholangiocarcinoma

Abstract: Background Cancer recurrence is the important problem of cholangiocarcinoma (CCA) patients, lead to a very high mortality rate. Therefore, the identification of candidate markers to predict CCA recurrence is needed in order to effectively manage the disease. This study aims to examine the predictive value of cancer stem cell (CSC) markers on the progression and recurrence of CCA patients. Methods The expression of 6 putative CSC markers, cluster of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…Recently, we reported the association of CSCs and recurrence with the overexpression of putative cancer stem-like cell (CSC) markers. These have the potential to predict CCA recurrence [ 7 ]. However, the mechanism involved in CCA recurrence is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the association of CSCs and recurrence with the overexpression of putative cancer stem-like cell (CSC) markers. These have the potential to predict CCA recurrence [ 7 ]. However, the mechanism involved in CCA recurrence is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our result also supports a previous study that found a high expression of cancer stem cell markers, CD44s, CD44v6 and CD44v8-10, associated with poor prognosis in early stage CCA patients. 36 CD44v8-10 is a variant isoform of CD44 that plays a role in the regulation of oxidative stress in tumors by stabilizing the cystine–glutamate transporter and promoting glutathione synthesis. 37 In OV induced hamster CCA tissues, the expression of CD44v8-10 was induced during bile duct transformation, and it was associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…HIST1H4A resulted highly up-regulated in exosomes released by NSCLC [ 47 ]. A recent study conducted on CCA patients showed that high expression of ALDH1A1 correlated with a more favorable prognosis [ 48 ]; in many studies, ALDH1A1 is a cancer stem cell marker and a suitable target for therapy and only its activity is associated to worse prognosis [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%